Weed management practices of smallholder rice farmers in Northwest Cambodia. (September 2020) - Chhun, Sokunroth; Kumar, Virender; Martin, Robert J.; Srean, Pao; Hadi, Buyung A.R.
Abstract: One-hundred farmers from lowland rice systems of Battambang province in Cambodia were surveyed in 2017 using a structured questionnaire with the objectives to (1) determine farmers' current knowledge and weed management practices and document the effect of adopted agronomic practices on management of weeds in rice, and (2) quantify the extent of weed seed contamination in farmers' own saved paddy seed lots. To estimate the level of contamination by weed seeds, a one kg paddy seed sample was collected from each surveyed farmer. All farmers practiced broadcast direct-seeded rice (DSR), with an average seeding rate of 181 kg ha −1 . For sowing the rice crop, 82% of farmers used their own saved seeds or bought seed from their neighbour. All the paddy seed samples were contaminated with seeds of 34 weed species with an average of 1, 070 weed seeds kg −1 of paddy seed. The most common weed contaminants in the seed samples were Oryza sativa f. spontanea (weedy rice), Fimbristylis miliacea, Echinochloa colona, Echinochloa crus-galli, and Ischaemum rugosum. Weeds, in their rice field, were considered a major problem by 93% of farmers with 70% of farmers indicating a yield loss of >20% due to weed competition. All farmers followed a post-emergence based herbicide program for weed control with no use of pre-emergence herbicides. Farmers (75%) relied on the advice of input dealers on the selection and use of herbicides. Knowledge gaps were found among farmers on herbicide application techniques including selection of the right sprayer, nozzle tips, and sprayer calibration. Although 94% of farmers responded that they were aware of pesticide exposure risk, use of boots and gloves, as personal protective equipment, during spraying was low (10 and 54%, respectively). The fertilizer use was lower than recommended rates (50% of recommended N and around 40% of recommended P and K). An exploitable rice yield gap of 1.3 t ha −1 (40%) and 1.1 t ha −1 (30%) was found in the wet and dry season, respectively. These results suggest that integrated weed management (IWM) and optimum fertilizer use can play an important role in closing the rice yield gap in Battambang. IWM options using clean/certified seeds free from weed seeds, optimum fertilizer, selection and application of appropriate pre- and post-emergence herbicides at the right time, amount, and accurate application techniques can improve weed control and hence enhance the rice yield in Cambodia. Farmer training is needed to close their knowledge gaps and to educate them on IWM, especially, to manage difficult-to-control weeds such as weedy rice. Highlights: Study was conducted in lowland rice environment of Battambang province in northwest Cambodia. Knowledge gaps in farmers' current weed and crop management practices identified. Level of weed seed contamination in farmers saved paddy seed quantified. 100% seed samples were contaminated with weed seeds with an average of 1070 seeds kg −1 of paddy seeds. Current practices such as high seed rate + contaminated paddy seed have a major impact on weed management in Cambodia.